Behavioral Economics in Advertising: Analyzing Consumer Decision-Making Patterns - Rina Sari; Budino Saputra (International Journal of Economics, Commerce, and Management, 2024)
Behavioral economics has emerged as a significant field in understanding consumer behavior, particularly in advertising. This paper examines the application of behavioral economics principles, such as scarcity, social proof, and emotional appeal, in influencing consumer decision-making. Through an in-depth analysis of advertising techniques across various industries, the study assesses their effectiveness and ethical implications, particularly in terms of consumer welfare. Results reveal that while these psychological triggers can effectively drive sales, they also present ethical concerns regarding consumer autonomy and well-being.